Establishing a Pathological Diagnosis in Degenerative Dementias - Lowe, James (Brain Pathol, 2006)
While clinicopathological studies have confirmed that Alzheimer's disease (AD) is the most common neurodegenerative cause of dementia, these same studies have also revealed that other degenerative pathologies account for a significant proportion of patients with cognitive decline. Because pathological assessment of non‐Alzheimer neurodegenerative diseases now demands routine use of a costly panel of immunohistochemical techniques a scheme for staged examination of brain tissue has been developed. This scheme is weighted to initially screen out cases of Alzheimer's disease, dementia with Lewy bodies and vascular dementia using conventional staining methods and established diagnostic protocols, bringing in immunochemical techniques to discriminate between non‐Alzheimer degenerative dementias. Diagnosis of pathologies causing the clinical syndrome of frontotemporal dementia can be ascertained using conventional staining supplemented by immunochemical detection of ubiquitin, tau protein and α B crystallin. The diagnosis of prion disease is reliably confirmed by immunohistochemical detection of prion protein. This morphological assessment complements emerging genetic insights into many of these neurodegenerative diseases.